Complications of inguinal hernia repair in children: A tertiary hospital experience - Chukwubuike, Kevin Emeka (Journal of Kathmandu Medical College, 2020)
Background: Repair of inguinal hernia is one of the most frequently performed procedures in pediatric surgery. Objective: The aim of this study was to evaluate the complications we encountered following repair of inguinal hernia in children. Methodology: This was a retrospective study done in children aged 15 years and below who had complications following inguinal hernia repair (both emergency and elective) at the pediatric surgery unit of Enugu State University Teaching Hospital (ESUTH) Enugu, Nigeria, between January 2014 and December 2018. Results: A total of 1243 cases of pediatric inguinal hernia repairs were performed during the study period. Out of this, 123 patients developed complications, accounting for 9.9% of the total cases. There was male predominance with a median age of 1 year. Most of the complications were noted in infants undergoing emergency repairs. Scrotal complications were the most common complications which resolved on non-operative treatment. Other complications in descending order of frequency included wound infection, hernia recurrence, testicular atrophy and sensory disturbances in the inguinal region. There was no mortality following the surgeries. Conclusion: Pediatric inguinal hernia repair is a procedure with potential complications more so in infants following an emergency repair. Preoperative parental counseling and timely referral are mandatory.